Pengaruh Keterampilan Kewirausahaan Perempuan Terhadap Peningkatan Pendapatan Di Kabupaten Jember - Anastasya Gawal Putri; Andini Istiqomah; Ning Nabila Zuhro (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
A skill in women's entrepreneurship is needed because it can increase income in the Jember Regency area. Women who have skills tend to be more able to start and run their businesses well. With good skills, it is also more possible for women to be more flexible in facing an economic challenge. A business also needs the right marketing strategy and in accordance with the target market to be targeted. This strategy is useful for facing challenges or obstacles that exist in a women's entrepreneurship. This study aims to determine the influence of women's entrepreneurial skills in increasing income in Jember Regency using Tony Barnett's theory of social movements. In this study, the research method used is qualitative with data collection techniques through observation, interviews, and documentation. The results of this study show that women's entrepreneurial skills in increasing income are still very effective to be carried out because these skills are useful for attracting the attention of customers to be interested in buying the products that have been offered. It needs to be improved in terms of promoting the products offered so that the social media owned is more crowded and the products are better known by many people, especially among students.